The Proto-Fuse project: methods to boost creativity for architects. Issue 3 (1st October 2016) - Mahdizadeh Hakak, Alireza; Bhattacharya, Joydeep; Biloria, Nimish; Ahmadi Venhari, Armaghan
Abstract : Human civilization can be ameliorated by human creativity. Innovation and progress of human civilization result from a change in our thinking patterns, thus, potentially transforming the present into a creative future. Accentuating the role of creativity in design even more than other disciplines pushes one to underpin the understanding of creativity as a key role player in architecture. Furthermore, by identifying the basic principles of our ingenuity/creativity, researchers might be able to enhance this ability in the future. The digital era allows for a new domain of architectural experience. It is assumed that new designs in virtual environments can be created that go beyond the mere accommodation of literal functions, and affect human experiences. This paper presents the role of a method developed by the authors: 'Proto-Fuse', experimented with, as an artwork for the survey of cognitive perception of humans, specifically targeting enhancement of spatial creativity. The logic behind this method is based on two psychological concepts: 1 – conceptual blending, 2 – tolerance of ambiguity. Two experimental projects were conducted for exploring the Proto Fuse method: (a) "unconventional virtual environments (UVEs)" to improve conceptual blending and (b) "Extracting local distance" to enhance tolerance of ambiguity. The paper concludes with an implementation scenario of the Proto-Fuse method in the pedagogy of architecture and elaborates on the results of the projects and analysis of the feedbacks received during the project session.